Phytochemical Composition and Biological Activity of the Essential Oil from Ericameria nauseosa Collected in Southwestern Montana, United States; Plants; Vol. 13, iss. 15 - Schepetkin (Shchepyotkin) I. A. Igor Aleksandrovich; Özek G. Gulmira; Özek T. Temel; Kirpotina L. N. Liliya Nikolaevna; Khlebnikov A. I. Andrey Ivanovich; Ayçiçek K. Kevser; Lavin M. Matthew; Quinn M. T. Mark (2024, 2024)
Title screen